The reporting of patient safety incidents by nurses in both outpatient and inpatient units of the hospital." at dr. M. Djamil Padang - Marpaung, Yahya; Hartati, Hartati; Karnita, Fera; Diana, Nesti; Ananda, Amatul Dhea (Science Midwifery, 2025)
This research aims to provide insights to the management of Dr. M. Djamil Padang General Hospital regarding the factors contributing to the decrease in incident reports, enabling the determination of follow-up steps, including policies aligned with the Analysis of Patient Safety Incident Reporting (PSIR) at Dr. M. Djamil Padang General Hospital in 2022. Method: This study employed a mixed-methods approach that combines quantitative and qualitative methods using a sequential explanatory design. The study population consisted of nursing staff in selected service units through proportionate random sampling, with five individuals participating in the qualitative research. Results: The implementation of the reporting system at Dr. M. Djamil Padang General Hospital was neither efficient nor optimal. Although health professionals submitted incident reports manually or directly through the application, the number of patient safety incident reports in 2022 showed a significant decrease, totaling 1,882 incidents compared with the previous year's 8,421 incidents. Barriers to incident reporting include motivation and fear, whereas knowledge regarding incident types and reporting is generally good. Conclusion: Quantitative research results indicate that respondents’ knowledge of patient safety incidents is relatively good, with over 50% answering questions related to patient safety incidents correctly. Qualitative research findings revealed obstacles contributing to the decline in patient safety incident reporting, including respondent motivation, workload, and fear.